Poor Performance at TVET Colleges: Conceptualising a Distributed Instructional Leadership Approach as a Solution - Badenhorst, Jo W.; Radile, Rachere S. (Africa Education Review, 2018)
In South Africa the challenges facing the post-school vocational education system are daunting. There is a lack of coherence, resulting in fragmentation of the system. A Training Needs Assessment Study commissioned in 2014 revealed several major academic challenges facing college leadership. The most pressing issues were poor leadership and management skills and challenges facing lecturers in various aspects of teaching and learning, amongst which were blatant shortcomings in their capabilities to meet the competencies required for effective lecturing. This realisation led the researchers to hypothesise that ineffective and fragmented leadership and management practices may be to blame for this state of affairs. The researchers wondered whether an integrated and focused leadership model aimed at distributing ownership for student achievement should be implemented to produce better results. The overarching research question was: What are the main stumbling blocks in improving National Certificate: Vocational (NC(V)) students’ performance at technical and vocational education and training (TVET) colleges; and how can a distributed instructional leadership approach be conceptualised to address the problems at institutional level? A qualitative research approach was used, which was mainly inductive, providing a clear understanding of the participants’ views and capturing their perceptions in their own words. A phenomenological design was used as strategy of inquiry. The findings created an awareness for considering collaboration and the distribution of powers and capabilities to bring about a shared leadership vision in the quest for challenging poor performance at institutional level in a sector that is in dire need of positive outcomes.
Published Article
Keywords: distributed instructional leadership; instructional leadership; phenomenological design; student learning outcomes; student performance; student support; technical; vocational education; training